Systematic Review of the Mediating and Moderating Mechanisms Between Digital Competence and Academic Performance in Higher Education - Nurlaili; Dina Martha Fitri; Bayu Saputra (Sakura Digital Nusantara, 2026)
Digital literacy has become a critical competency in higher education, yet its relationship with academic performance remains insufficiently understood due to fragmented empirical evidence. This systematic literature review synthesizes findings from 42 peer-reviewed studies published between 2010 and 2025, identified through Scopus, Web of Science, and ERIC databases following PRISMA 2020 guidelines. The synthesis reveals that 85.7% of included studies reported a positive association between digital literacy and academic performance, with effect sizes ranging from r = 0.34 to r = 0.62. Importantly, the evidence suggests that this relationship is not direct but operates through psychological mediators, particularly self-efficacy and self-regulated learning, and is conditioned by structural moderators including institutional infrastructure, socioeconomic status, and disciplinary context. Unlike previous reviews that predominantly examined direct effects, this study proposes the Digital-Ecological Nexus framework, integrating Social Cognitive Theory and Ecological Systems Theory to conceptualize the multi-pathway, conditionally dependent nature of this relationship. The framework offers a synthesis-derived moderated-mediation model that accounts for both individual agency and contextual boundary conditions. These findings provide evidence-based directions for educational policy and pedagogical design, while future research should prioritize longitudinal designs and formal validation of the proposed framework.